Effects of mind-body exercises on cognitive impairment in people with Parkinson's disease: A mini-review - Zhang, Ting; Liu, Wei; Gao, Song (Frontiers in Neurology, 2022)
Parkinson's disease (PD) is an important health problem caused by the degeneration of brain neurons. Bradykinesia and lower balance ability seriously affect the quality of life of people with PD. Non-motor symptoms, such as cognitive impairment, accompany the course of the disease but still lack sufficient attention. In general, drugs combined with cognitive training are the most common ways to improve cognitive impairment in people with PD. However, long-term use of psychiatric drugs may lead to side effects such as brain death and movement disorders. Recently, mindfulness has been used by researchers in the treatment of cognitive impairment, because healthy older adults who engage in mind-body exercises for a long time have higher cognitive levels than normal aging populations. Mind-body exercise, as a therapy that combines concentration, breath control, and physical activity, is beneficial for improving practitioners' brain and mental health. Mind-body exercises such as Tai Chi, yoga, dance, and Pilates can improve cognitive performance in older adults with or without cognitive impairment. Therefore, mind-body exercise may be a feasible strategy for the treatment of cognitive impairment in people with PD. This study summarizes the latest evidence that mind-body exercises including Tai Chi, Qigong, yoga, and dance improve cognitive impairment associated with PD. We also explored the limitations of current mind-body exercise research, aiming to provide new ideas for improving mind-body exercise as a strategy to alleviate cognitive impairment in people with PD.